Ceria-engineered nanomaterial distribution in, and clearance from, blood: size matters. (January 2012) - Dan, Mo; Wu, Peng; Grulke, Eric A; Graham, Uschi M; Unrine, Jason M; Yokel, Robert A
Aims: Characterize different sized ceria-engineered nanomaterial (ENM) distribution in, and clearance from, blood (compared to the cerium ion) following intravenous infusion.Materials & Methods: Cerium (Ce) was quantified in whole blood, serum and clot (the formed elements) up to 720 h.Results: Traditional pharmacokinetic modeling showed best fit for 5 nm ceria ENM and the cerium ion. Ceria ENMs larger than 5 nm were rapidly cleared from blood. After initially declining, whole blood 15 and 30 nm ceria increased (results that have not been well-described by traditional pharmacokinetic modeling). The cerium ion and 5 and 55 nm ceria did not preferentially distribute into serum or clot, a mixture of cubic and rod shaped ceria was predominantly in the clot, and 15 and 30 nm ceria migrated into the clot over 4 h.Conclusion: Reticuloendothelial organs may not readily recognize five nm ceria. Increased ceria distribution into the clot over time may be due to opsonization. Traditional pharmacokinetic analysis was not very informative. Ceria ENM pharmacokinetics are quite different from the cerium ion.